(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Language is one of the complicated and dynamic of communication that involves the usage of symbols, sounds or gestures to convey the meaning. However, what is language acquisition actually, and what are it’s differences with language learning? The terms “language acquisition” and “language learning” may seem interchangeable, but they are completely different. Fundamentally, language learning involves a conscious, intentional effort to acquire linguistic knowledge through active study and formal teaching methods. It follows a structured approach, often observed in classroom settings, where individuals actively delve into understanding grammar rules, expanding vocabulary and grasping linguistic nuances.